Strategi Pembelajaran Berbasis Masalah dan Strategi Pembelajaran Peningkatan Kemampuan Berpikir (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Education in the modern era requires students not only to master cognitive knowledge, but also to have the ability to think critically, analytically, creatively, and problem solving skills independently. Therefore, the application of the Problem Based Learning (PBL) model and the Learning Strategy for Improving Thinking Ability (SPPKB) is considered relevant and ideal in the context of Christian Religious Education (PAK) to integrate faith values with the reality of daily life. This study uses a literature study method by examining scientific journals, books, and academic articles to analyze the definition, essence, characteristics, and steps of PBL which include the introduction of authentic cases, problem solving, investigation planning, independent learning, solution synthesis, presentation of results, and reflection. PBL has proven to be effective in increasing learning motivation, collaboration, and internalization of Christian moral values, although it has limitations in the relatively long time requirement and the demands of teacher competence as facilitators. Meanwhile, SPPKB emphasizes intellectual stimulus, exploration of ideas, data processing, in-depth analysis, and metacognitive reflection to form a systematic and independent mindset in dealing with religious ethical issues. These two student-centered learning strategies complement each other in forming students who are dynamic, reflective, critical, and responsible as Christian personalities through flexible and contextual learning adaptations in PAK.